THE LEGAL FRAMEWORK ISSUES OF PMSC: INDONESIAN PRACTICE - Muhammad Ardiansyah Arifin (Faculty of Law, Universitas Gadjah Mada, 2022)
Abstract A form of private security contractor exists for maritime security called Private Maritime Security Company (PMSC). PMSCs are not abundant in maritime law scholarly discourse. This underappreciation happens despite the importance of PMSC in Malacca Strait that conducts its services in the jurisdiction of the three littoral states of Indonesia, Malaysia, and Singapore. Hence, this research article will find out the legal frameworks of the PMSC industry both in the international regime and Indonesian regime and the legality of PMSC business in Indonesia. The method used in this research is normative legal research method with statute approach, historical approach, conceptual approach, and comparative approach with sources from secondary sources which include but are not limited to primary legal sources and secondary legal sources. The result from this research highlights the existence of an international non-binding legal framework for PMSC and a legal framework for PMSC in Indonesia. However, there are legal problems concerning the status of passage and PMSC compliance with domestic laws. A recommendation for a legally binding multilateral treaty about PMSC would be a start to increase the legal certainty of PMSC business internationally. At the same time, a domestic regulation in Indonesia that has specific scope in PMSC would allow PMSC business to be better regulated and grown in Indonesia as a legitimate sector.AbstrakSebuah bentuk keamanan swasta untuk keamanan maritim disebut Private Maritime Security Company (PMSC). PMSC kurang dibahas dalam wacana ilmiah hukum maritim. Kurangnya apresiasi ini terjadi meskipun PMSC di Selat Malaka sangat penting dalam menjalankan tugasnya di wilayah hukum littoral states yaitu Indonesia, Malaysia, dan Singapura. Oleh karena itu, artikel penelitian ini akan menganalisis kerangka hukum industri PMSC baik di hukum internasional maupun hukum Indonesia serta legalitas bisnis PMSC di Indonesia. Metode yang digunakan dalam penelitian ini adalah metode penelitian hukum normatif dengan pendekatan undang-undang, pendekatan historis, pendekatan konseptual, dan pendekatan komparatif dengan sumber-sumber dari sumber sekunder yang meliputi tetapi tidak terbatas pada sumber hukum primer dan sumber hukum sekunder. Hasil dari penelitian ini menyoroti adanya kerangka hukum internasional yang tidak mengikat bagi PMSC dan kerangka hukum bagi PMSC di Indonesia. Namun, ada masalah hukum mengenai status bagian dan kepatuhan PMSC dengan hukum domestik. Rekomendasi perjanjian multilateral yang mengikat secara hukum tentang PMSC akan menjadi awal untuk meningkatkan kepastian hukum bisnis PMSC secara internasional. Pada saat yang sama, regulasi domestik di Indonesia yang memiliki ruang lingkup khusus dalam PMSC akan memungkinkan bisnis PMSC diatur dengan lebih baik dan tumbuh di Indonesia sebagai sektor yang sah.